Pokolenia transformacji - relacje społeczne, doświadczenia, strategie młodych po 1990 r. = Transformation Generatiom - Social Reports, Experiences, Strategies of the Young after 1990 - Sińczuch, Marcin (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to present selected areas of social functioning of consecutive generations of young people who entered adulthood after 1990. I will be most interested in the relationship between a realm of objective social facts, represented by economic factors -especially concerning labour market, and the area of social relationship in the family and between young people comprising communication, spending time together and satisfaction with the relationship.
Keywords: transformacja ustrojowa; relacje rodzinne; relacje społeczne; młodzież; Polska